2019
DOI: 10.3389/fpsyg.2019.02007
|View full text |Cite
|
Sign up to set email alerts
|

Primes and Consequences: A Systematic Review of Meritocracy in Intergroup Relations

Abstract: Psychological interest in Meritocracy as an important social norm regulating most of the western democratic societies has significantly increased over the years. However, the way Meritocracy has been conceptualized and operationalized in experimental studies has advanced in significant ways. As a result, a variety of paradigms arose to understand the social consequences of Meritocracy for intergroup relations; in particular, to understand the adverse consequences of Meritocracy for disadvantaged group members.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 79 publications
(172 reference statements)
2
44
0
Order By: Relevance
“…As there is a strong emphasis on meritocracy in Singapore, stigma towards mental illness may arise due to the fact that many PMI have histories of disrupted academic or vocational careers, both of which happen to be highly valued in a meritocratic society. Furthermore, meritocracy facilitates negative evaluations and stereotyping towards 'low status' groups, as highlighted by a systematic review [58]. A plausible explanation for this is that because meritocratic worldviews are typically associated with the beliefs of a just world (i.e., I get what I deserve), it leads to a perception that PMI are responsible for their own illness and their inability to achieve in life [59].…”
Section: Discussionmentioning
confidence: 99%
“…As there is a strong emphasis on meritocracy in Singapore, stigma towards mental illness may arise due to the fact that many PMI have histories of disrupted academic or vocational careers, both of which happen to be highly valued in a meritocratic society. Furthermore, meritocracy facilitates negative evaluations and stereotyping towards 'low status' groups, as highlighted by a systematic review [58]. A plausible explanation for this is that because meritocratic worldviews are typically associated with the beliefs of a just world (i.e., I get what I deserve), it leads to a perception that PMI are responsible for their own illness and their inability to achieve in life [59].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a paradox within Meritocracy [ 45 ] that is seen as deriving from an equity principle but has been associated to the underestimation of inherent inequalities [ 46 ] and to their justification [ 47 ]. A systematic review [ 48 ] has shown that its endorsement negatively affects low-status group members. These results have been described in important fields, such as in organizations [ 49 ], schools [ 50 ] and reparation policies [ 51 ], but only tangentially in decisions within the criminal justice system [ 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results have been described in important fields, such as in organizations [ 49 ], schools [ 50 ] and reparation policies [ 51 ], but only tangentially in decisions within the criminal justice system [ 52 , 53 ]. We argue that the results are tangential as these studies focused on the Protestant Work Ethic [ 54 ], a norm that shares the dimension of effort-based success with Meritocracy but it is seen only as a component of it [ 48 ] and because it does not differentiate decisions towards racialized groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the strength of the relationship between conservative views and our behavioural effects indicates the robustness of this effect. On the other hand, exposure to a Protestant work ethic could be a factor influencing our behavioural results, making our findings particularly relevant for western societies where the debate on meritocracy is particularly intense 53 .…”
Section: Discussionmentioning
confidence: 93%